Biphenyl and Benzoate Metabolism in a Genomic Context: Outlining Genome-Wide Metabolic Networks in Burkholderia xenovorans LB400 - Denef, V. J. (American Society for Microbiology, 2004)
We designed and successfully implemented the use of in situ-synthesized 45-mer oligonucleotide DNA microarrays (XeoChips) for genome-wide expression profiling of Burkholderia xenovorans LB400, which is among the best aerobic polychlorinated biphenyl degraders known so far. We conducted differential gene expression profiling during exponential growth on succinate, benzoate, and biphenyl as sole carbon sources and investigated the transcriptome of early-stationary-phase cells grown on biphenyl. Based on these experiments, we outlined metabolic pathways and summarized other cellular functions in the organism relevant for biphenyl and benzoate degradation. All genes previously identified as being directly involved in biphenyl degradation were up-regulated when cells were grown on biphenyl compared to expression in succinate-grown cells. For benzoate degradation, however, genes for an aerobic coenzyme A activation pathway were up-regulated in biphenyl-grown cells, while the pathway for benzoate degradation via hydroxylation was up-regulated in benzoate-grown cells. The early-stationary-phase biphenyl-grown cells showed similar expression of biphenyl pathway genes, but a surprising up-regulation of C(1) metabolic pathway genes was observed. The microarray results were validated by quantitative reverse transcription PCR with a subset of genes of interest. The XeoChips showed a chip-to-chip variation of 13.9%, compared to the 21.6% variation for spotted oligonucleotide microarrays, which is less variation than that typically reported for PCR product microarrays.